2023
DOI: 10.1186/s12916-023-02965-w
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for human papillomavirus infection, cervical intraepithelial neoplasia and cervical cancer: an umbrella review and follow-up Mendelian randomisation studies

Abstract: Background Persistent infection by oncogenic human papillomavirus (HPV) is necessary although not sufficient for development of cervical cancer. Behavioural, environmental, or comorbid exposures may promote or protect against malignant transformation. Randomised evidence is limited and the validity of observational studies describing these associations remains unclear. Methods In this umbrella review, we searched electronic databases to identify me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 110 publications
0
17
0
Order By: Relevance
“…Other genetic and life style factors can increase chances of HPV infection ( Haukioja, 2014 ). HIV has been categorically proven to be a risk factor for HPV persistence ( Bowden, 2023 ) which in turn increases expression of P16ink4A. This further explains the observation of raised P16ink4A serum concentrations in control groups, who were mostly HIV positive, compared to controls.…”
Section: Discussionmentioning
confidence: 92%
“…Other genetic and life style factors can increase chances of HPV infection ( Haukioja, 2014 ). HIV has been categorically proven to be a risk factor for HPV persistence ( Bowden, 2023 ) which in turn increases expression of P16ink4A. This further explains the observation of raised P16ink4A serum concentrations in control groups, who were mostly HIV positive, compared to controls.…”
Section: Discussionmentioning
confidence: 92%
“…These emerging scenarios prompt new studies focusing not only on the relationship between imiquimod and HPV but also on its interactions within the vaginal microbiome, aiming to discern which patients should receive imiquimod treatment as an alternative to conization surgery. Other factors such as HIV infection and the use of immunosuppressive drugs that may affect the immune response against HPV could also impact the response to imiquimod and should be considered 98 . Interestingly, a recent pilot study showed good efficacy by combining imiquimod with topical 5‐fluorouracil for CIN 2‐3, 75 but we need further results for the efficacy of this drug combination.…”
Section: Discussionmentioning
confidence: 99%
“…HPV infection is a well‐established cause of cervical oropharyngeal, anal, penile, vaginal, and vulvar cancers, and of other associated diseases, including cutaneous and anogenital warts 3 . Certain other risk factors such as smoking, may influence which women exposed to HPV are more likely to develop cervical cancer 4 . In addition, some coinfected pathogens, such as human immunodeficiency virus (HIV) and chlamydia, have been reported to increase the risk of women exposed to HPV for developing cervical cancer 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…3 Certain other risk factors such as smoking, may influence which women exposed to HPV are more likely to develop cervical cancer. 4 In addition, some coinfected pathogens, such as human immunodeficiency virus (HIV) and chlamydia, have been reported to increase the risk of women exposed to HPV for developing cervical cancer. 5,6 An oncovirus or oncogenic virus is a virus that can cause cancer.…”
mentioning
confidence: 99%